Sarcopenia in Type 2 Diabetes Mellitus: A Cross-Sectional Observational Study - L. M. Pechmann; T. H. Jonasson; V. S. Canossa; H. Trierweiler; G. Kisielewicz; R. R. Petterle; C. A. Moreira; V. Z. C. Borba (International Journal of Endocrinology)
Background. The aim of this study was to compare the prevalence of low muscle mass and sarcopenia in patients with type 2 diabetes mellitus (T2DM) versus paired controls (control group, CG) and the association between sarcopenia and chronic diabetes complications. Methods. Men and women ≥50 years with T2DM (T2DM group, T2DMG) were recruited during routine outpatient visits. Total body densitometry and handgrip strength (HGS) were evaluated in the T2DMG and CG, while the T2DMG was also evaluated for the physical performance using the gait speed (GS) test. Sarcopenia was diagnosed according to the criteria of the Foundation for the National Institutes of Health Sarcopenia Project (FNIH). Results. The study included 177 individuals in the T2DMG and 146 in the CG. The mean HGS value was lower in the T2DMG (24.4 ± 10.3 kg) compared with the CG (30.9 ± 9.15 kg), p<0.001, with low HGS in 46 (25.9%) and 10 (9%) in the T2DMG and CG, respectively (p<0.001). The prevalence of sarcopenia defined according to the FNIH criteria was higher in the T2DMG 23 (12.9%) compared with the CG 8 (5.4%), p<0.03. The presence of albuminuria increased the odds of sarcopenia (odds ratio (OR) 2.84, 95% confidence interval (CI) 1.07–7.68, p=0.04) and osteoporosis (OR 3.38, 95% CI 1.12–9.89, p=0.03), even in patients with mild to moderate nephropathy. The body composition analysis showed increased odds of sarcopenia with increased percentage of total fat (%TF) in women (OR 1.18, 95% CI, 1.03–1.43, p=0.03) and men (OR 1.31, 95% CI, 1.10–1.75, p=0.01). Conclusion. Patients with T2DM presenting with albuminuria, osteoporosis, and increased %TF were more likely to have sarcopenia. This finding emphasizes the need for patients with T2DM to be evaluated for sarcopenia to allow for early implementation of measures to prevent or treat this disorder.